PENGARUH GOOD CORPORATE GOVERNANCE PADA KINERJA PERUSAHAAN SEKTOR PELAYANAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - Deta, Yohanis Umbu; Amtiran, Paulina Yuritha; Foenay, Christien Corina (Universitas Nusa Cendana, 2024)
This research aims to analyse the effect of good corporate governance on proxied performance, consisting of independent commissioners, managerial ownership, institutional ownership, and audit committee independence on the performance of transportation sector service companies listed on the Indonesian stock exchange in 2016-2020. This study used quantitative methods, the calculations using the Eviews 9.0 application program. The results of this study and the discussion found that good corporate governance has a positive and negative influence. Partially, the independent board of commissioners is not positively influential and significant, managerial ownership is not influential and significant, institutional ownership is not influential and significant and the independence of the audit committee has a significant and negative influence on the company’s performance. Simultaneously, all variables have a significant positive effect on the company. The results of this study can be used as objects for transportation sector service companies that aim to improve performance, especially the company's operational activities, and can improve the capabilities of all components of the company. Keywords: Independent Commissioners; GCG; Managerial Ownership; Institutional Ownership and Audit Committee Independence; ROA